Pope Leo XIV: The Indonesian Church with Dialogue as a Form of Togetherness for Peace - Tinambunan, Edison R.L. (Studia Philosophica et Theologica, 2025)
This paper will examine Pope Leo XIV's teachings on dialogue and their implications for the Indonesian church. The method used to study Pope Leo's teachings on dialogue is to quote his direct statements as reported by Vatican News. This method shows that the sources used are primary, which are oriented towards the originality of his teachings. This research system uses an applied qualitative methodology with analysis and synthesis of direct statements placed within the findings. A table of direct quotations related to dialogue will be presented, which will then be analysed and synthesised to determine their implications for the Indonesian church in working together to achieve peace. This research aims to demonstrate the role of dialogue as a means of achieving peace in Indonesia, which is also the spirit of this country. Through its faithful, the Indonesian church has two foundations for dialogue within itself that make it a bridge and a promoter of peace through its way of life. One is a theological-Christological foundation, and the other is a state foundation, based on deliberative consensus.